Genome Sequence and Analysis of Peptoclostridium difficile Strain ZJCDC-S82. (January 2016) - Luo, Yun; Huang, Chen; Ye, Julian; Fang, Weijia; Gu, Wanjun; Chen, Zhiping; Li, Hui; Wang, XianJun; Jin, Dazhi
Peptoclostridium difficile ( Clostridium difficile ) is the major pathogen associated with infectious diarrhea in humans. Concomitant with the increased incidence of C. difficile infection worldwide, there is an increasing concern regarding this infection type. This study reports a draft assembly and detailed sequence analysis of C. difficile strain ZJCDC-S82. The de novo assembled genome was 4.19 Mb in size, which includes 4, 013 protein-coding genes, 41 rRNA genes, and 84 tRNA genes. Along with the nuclear genome, we also assembled sequencing information for a single plasmid consisting of 11, 930 nucleotides. Comparative genomic analysis of C. difficile ZJCDC-S82 and two other previously published strains, such as M120 and CD630, showed extensive similarity. Phylogenetic analysis revealed that genetic diversity among C. difficile strains was not influenced by geographic location. Evolutionary analysis suggested that four genes encoding surface proteins exhibited positive selection in C. difficile ZJCDC-S82. Codon usage analysis indicated that C. difficile ZJCDC-S82 had high codon usage bias toward A/U-ended codons. Furthermore, codon usage patterns in C. difficile ZJCDC-S82 were predominantly affected by mutation pressure. Our results provide detailed information pertaining to the C. difficile genome associated with a strain from mainland China. This analysis will facilitate the understanding of genomic diversity and evolution of C. difficile strains in this region.